Best Practices for Stakeholder Engagement for Government R&D Organizations. Issue 1 (2nd January 2023) - Beam, Carrie; Specking, Eric; Parnell, Gregory S.; Pohl, Ed; Goerger, Maria N.; Buchanan, J. Paige; Gallarno, George E.
Abstract: This paper identifies best practices for stakeholder engagement for Research & Development (R&D) organizations, describes findings, and makes recommendations. We identify 106 best practices for stakeholder engagement, which came from 19 sources, including corporate publications, governmental sources, standards organizations, and other similar organizations. We identify sources, review them for best practices, place the best practices into a database, group the best practices, and document our findings. We group these best practices into the seven separate objectives: 1) identify stakeholders, 2) diversify stakeholder relationships, 3) improve stakeholder communication, 4) increase all stakeholder engagement activity, especially strategic and customer stakeholder engagement activities, 5) manage stakeholder expectations, 6) increase stakeholder value and alignment, and 7) increase strategic stakeholder relationship strength. Two important best practice findings are that (a) stakeholder engagement should be a dynamic, ongoing process and (b) R&D organizations should systematically identify and prioritize strategic stakeholder engagements. We recommend that R&D organizations develop a decision support tool to identify and prioritize strategic stakeholder engagements, and then use this tool to develop and implement strategic engagement plans.